(untitled) (Journal of International Studies, 2025)
Maritime security governance of a strategic ‘strait’ is unique. It is a complex exercise for coastal states, in particular, to have control over adjacent offshore resources, navigational rights, and maintaining access to commercial and military vessels passing through the waterway. Central to this is sustaining a balanced governance approach to security that would impinge on navigational freedom and coastal states’ rights and duties. However, maritime security governance is not only the actions of a sovereign state or a group of sovereign countries but also non-sovereign entities and institutions. It includes the formulation and implementation of solutions to collective issues. Several factors, such as historical patterns of regulation and control of the policy sector and institutional interests, eventually influence states in either promoting or resisting the formation of governance mechanisms. While maritime security governance exists in many international straits, the focus of this article is on the Straits of Malacca (Strait of Malacca and Strait of Singapore), hereafter referred to as SOM, a strategic maritime passage that involves multiple interests involving governance, military, and commercial aspects. Maritime security governance is at the core of the SOM’s management. Indonesia, Malaysia, and Singapore’s approaches towards maritime security are strongly influenced by their sovereign, economic, and legal interests. This article is divided into three sections. First, it defines the concept of governance and examines why maritime security governance has garnered attention in contemporary international relations. Second, it identifies maritime security governance approaches among the littoral states in the SOM. Third, it explains why the littoral states adopt diverging approaches to security governance and the conditions shaping their attitudes.